PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN (STUDI PADA KONSUMEN COFFEE CORNER SURABAYA) - CANDRA PERTIWI, DWI (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
As development era, wide spread of coffee shop cause increasing the level of competition. The services quality and price as an element of marketing mix it has been reviewed further to maintain consumer satisfaction on Coffee Corner Surabaya. This research test two independent variable that is the service quality, and the price that can affect the dependent variable for which is consumer satisfaction. Population in this research is consumers Coffee Corner Surabaya. Samples taken as many as 165 respondent with uses the technique non probability of sampling with the approach purposive of sampling. The Data is collected by using the method survey through a questionnaire that is filled by the consumer. Then the data analysis by the use of multiple regression analysis. This analysis, includes: test the validity, reliability test, the classical assumption test, multiple regression analysis, test the hypothesis through the test t- and F, a coefficient of determination and analysis (R²).Of regression analysis obtained as follows, equation Y= -0,660+0,234+0,537. Variable price has the most influence on consumer satisfaction of 0,537, later followed by the variable rates service quality amounted to 0,234. Result of the analysis using the t-test can be known that two independent variables namely service quality (X1) and price (X2) partially affect the dependent variable significantly to consumer satisfaction. Then use the F-test analysis result can be known that two independent variables namely services quality (X1) and price (X2) together affect the dependent variable significantly to consumer satisfaction. Result of the analysis using the coefficient of determination in mind that 0,536 or 53,6% of the variation of consumer satisfaction can be explained by the service quality and price. While the rest of the 0,464 or 46,4% explained by other variable which is not found in this research. Keyword : service quality, price, consumer satisfaction